CXCR5 engineered human and murine Tregs for targeted suppression in secondary and tertiary lymphoid organs - Doglio, Matteo; Rana, Jyoti; Stucchi, Adriana; Melero, Maite-Muñoz; Ugolini, Alessia; Jofra, Tatiana; Toma, Cristiano; Bercher-Brayer, Clara; Carulli, Pierluigi; Kumar, Sandeep; Monti, Paolo; Martini, Elisa; et al. (Frontiers in Immunology, 2025)
IntroductionSecondary and tertiary lymphoid structures are a critical target of suppression in many autoimmune disorders, protein replacement therapies, and in transplantation. Although antigen-specific regulatory T cells (Tregs), such as chimeric antigen receptor (CAR) Tregs, generally persist longer and localize to target tissues more effectively than polyclonal Tregs in animal models, their numbers still progressively decline over time. A potential approach to maximize Treg activity in vivo is the expression of chemokine receptors such as CXCR5, which would enable localization of a greater number of engineered cells at sites of antigen presentation. Indeed, CXCR5 expression on follicular T helper cells and follicular Tregs enables migration toward lymph nodes, B cell zones, and tertiary lymphoid structures that appear in chronically inflamed non-lymphoid tissues.MethodsIn this study, we generated human and murine CXCR5 co-expressing engineered receptor Tregs and tested them in preclinical mouse models of allo-immunity and hemophilia A, respectively. Additionally, we engineered a murine CXCR5 co-expressing clotting factor VIII (FVIII) specific T cell receptor fusion construct epsilon (FVIII TRuCe CXCR5) Treg to suppress anti-drug antibody development in a model of FVIII protein replacement therapy for hemophilia A.ResultsIn vitro, anti-HLA-A2 CXCR5+ CAR-Tregs showed enhanced migratory and antigen-specific suppressive capacities compared to untransduced Tregs. When injected into an NSG mouse model of HLA-A2+ pancreatic islet transplantation, anti-HLA-A2 CXCR5+ CAR-Tregs maintained a good safety profile allowing for long-term graft survival in contrast to anti-HLA-A2 CXCR5+ conventional CAR-T (Tconv) cells that eliminated the graft. Similarly, FVIII TRuCe CXCR5 Treg demonstrated increased in vivo persistence and suppressive capacity in a murine model of hemophilia A.DiscussionCollectively, our findings indicate that CXCR5 co-expression is safe and enhances in vivo localization and persistence in target tissues. This strategy can potentially promote targeted tolerance without the risk of off-target effects in multiple disease models.